2008
DOI: 10.3758/lb.36.3.200
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the response in Simon discriminations by pigeons

Abstract: Spence (1952) postulated that under some conditions, responding in simple discriminations is controlled by compounds or patterns consisting of the nominal discriminative cue, plus its spatial position. Stimulus control by such compounds was said to develop when no single cue or element was systematically reinforced more than any other. This analysis has been applied to good effect in understanding some peculiar accuracy results obtained from pigeons performing Simon discrimination tasks. This article describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…Similar results have been reported for monkeys and for rats (Iversen, 1997;Iversen, Sidman, & Carrigan, 1986; see also Sidman, 1992). In short, a stimulus consistently appearing in one location may not function as the same stimulus when later shown in a different location (Urcuioli, 2007; see also Urcuioli, 2008c).…”
Section: Other Stimulus Class Assessments and The Functional Stimulussupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results have been reported for monkeys and for rats (Iversen, 1997;Iversen, Sidman, & Carrigan, 1986; see also Sidman, 1992). In short, a stimulus consistently appearing in one location may not function as the same stimulus when later shown in a different location (Urcuioli, 2007; see also Urcuioli, 2008c).…”
Section: Other Stimulus Class Assessments and The Functional Stimulussupporting
confidence: 80%
“…"Know the functional stimulus" is an especially important message because it is so easily overlooked, something I have experienced firsthand. Stimulus control has long been my primary area of research, yet I have on occasion devoted unnecessarily large amounts of time to understanding certain results (e.g., Urcuioli, 2006bUrcuioli, , 2008c that would have been far less time consuming had I listened to my own message and had a less anthropocentric view of the nature of the functional stimuli.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…In summary, Experiment 1 showed that rats can acquire a complex set of successive conditional discriminations using olfactory stimuli with schedule parameters based on Urcuioli (). However, there was little evidence of symmetry even after training that established the prerequisite relations that have been sufficient to produce symmetry in pigeons (Campos, Urcuioli & Swisher, ; Urcuioli, ; ; Urcuioli & Swisher, ). The procedures were closely patterned after the experimental strategy used by Urcuioli and his colleagues with pigeons, but several changes were necessary to make the transition to rats and olfactory stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…Urcuioli's () theory was explicitly designed to address emergent stimulus control in pigeons (cf. Urcuioli, ), but it seems possible that it might be more generally applicable to account for failure to show emergent symmetry in other nonhuman species. However, the failure to find symmetry in the present study suggests that for rats, at least with olfactory stimuli, stimulus control topographies develop differently than those observed in pigeons with visual stimuli during go/no‐go training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation